Model End-To-End Integrated Quality Management - A. Nazarenko, M.; A. Filippov, A.; V. Ants, V.; A. Baranova, I.; Yu. Cheremukhina, Yu.; S. Novikov MIREA, A. (International Journal of Engineering and Technology, 2018)
In this work, a model of end-to-end integrated quality management is developed, based on a set of existing models of enterprise operation, performance assessment and customer satisfaction ratings. The developed model integrates quality assessments by key parameters with the help of fuzzy regulators, which allow specifying estimates described in natural language.Â Â Â